Sustainable Grain Maize Production In A Gliricidia Alley Cropping System - Zawawi, Norziana Zin (2007)

(untitled)
Crop production under Ultisols in the humid tropics is usually limited by N deficiency and acid soil infertility problems. Effectiveness of legume residues as a nitrogen source is generally known to improve crop productivity by enhancing the availability of soil N where chemical fertilizer use often leads to deterioration in environmental quality. The aim of the study was to evaluate Gliricidia sepium residues (leaves and roots) as a potential source of N for a sustainable grain maize production in an alley cropping system in the tropics. In order to identify the determinants of the N dynamics of the Gliricidia sepium residues (leaves and roots), a laboratory incubation experiment was carried out with an Ultisols amended with Gliricidia sepium leaves, roots and their mixtures for 50 days. Quality of Gliricidia sepium residues was in order of leaves > mixtures > roots. The nitrogen and carbon mineralization also followed the same sequence (P<0.05) and this observation suggests that the potential of Gliricidia sepium residues to increase soil inorganic N depends on their quality. Results obtained showed that the Gliricidia sepium residues treatment was able to mitigate the soil acidity. The addition of Gliricidia sepium residues also increased major soil nutrient availability such as N, P, K, Ca and Mg. An experiment was carried out in semi-field conditions to compare the 15N labeling technique for estimating maize crop N uptake from Gliricidia sepium leaves and roots using direct 15N labeling and 15N dilution method. Results indicate that N contributed by Gliricidia sepium leaves to maize measured by direct 15N labeled and 15N dilution method were not significantly different (P>0.05). The percentage of nitrogen derived (%Ndfr) from the Gliricidia sepium 15N labeled leaves (direct labeling) was 26.9% and 41.9% from unlabeled leaves (15N dilution) in maize stover. Meanwhile, in maize cob, the %Ndfr from Gliricidia sepium leaves was 24.3% using 15N direct labeling and 46.4% using 15N dilution method. A field study was conducted using the 15N dilution method on N contribution from Gliricidia sepium leaves either integrated with or without additional urea fertilizer, or, with or without the presence of hedgerows. There was no significant difference (P>0.05) in maize yield upon application of Gliricidia sepium leaf mulch with urea fertilizer (LM+FERT) compared to Gliricidia sepium leaf mulch only (LM), suggesting that without additional amount of urea, in situ Gliricidia sepium leaf pruning is equally effective in maize production.